2019
DOI: 10.3390/electronics8101192
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Energy Consumption and Optimization Techniques for Writing Energy-Efficient Code

Abstract: The unprecedented growth of connected devices, together with the remarkable convergence of a wide variety of technologies, have led to an exponential increase in the services that the internet of things (IoT) can offer, all aimed at improving quality of life. Consequently, in order to meet the numerous challenges this produces, the IoT has become a major subject of research. One of these challenges is the reduction of energy consumption given the significant limitations of some devices. In addition, although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Two parameters are evaluated, which were Efficiency and Security. For efficiency, the raspberry 3B+ researcher decides 800 mA as default power usage [31]. Raspberry power usage with Rasefiberry hardware is connected to USB, CPU usage over 90 percent, and running openHAB as the IoT.…”
Section: Resultsmentioning
confidence: 99%
“…Two parameters are evaluated, which were Efficiency and Security. For efficiency, the raspberry 3B+ researcher decides 800 mA as default power usage [31]. Raspberry power usage with Rasefiberry hardware is connected to USB, CPU usage over 90 percent, and running openHAB as the IoT.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the rising complexity of IoT data transmission, storage, and processing capabilities requires more power-intensive tasks. In this sense, the capacity of IoT devices to operate for long periods without recharging is a significant challenge [96], [98], [99]. Finally, the rise of IoT and the emergence of LPWAN IoT technologies, e.g., in traffic monitoring, PA and animal health monitoring, posed an additional challenge to power efficiency in long-range transmission situations [96], [100].…”
Section: A Power Consumption (Reliable and Permanent Power Source)mentioning
confidence: 99%
“…Previous studies have shown that 40% of energy is consumed in buildings, including homes, offices, and hospitals [1]. These days, smart buildings are equipped with RnEs as a power supply that is controlled via an energy management system (EMS).…”
Section: Introductionmentioning
confidence: 99%